2001
DOI: 10.1161/01.str.32.4.855
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Chlamydia pneumoniae in Human Symptomatic and Asymptomatic Carotid Atherosclerotic Plaque

Abstract: Background-Chlamydia pneumoniae has been identified in atherosclerotic plaques of patients with cerebrovascular and cardiovascular disease. However, the direct causative effect of C pneumoniae infection in the activation of atherosclerotic plaque to a prothrombotic state remains to be established. The aim of the present study is to examine the correlation between intraplaque presence of chlamydiae and symptomatic carotid disease in humans. Methods-Plaques from 37 symptomatic and 57 asymptomatic consenting pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1
2

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 38 publications
4
64
1
2
Order By: Relevance
“…Infection appeared to be unrelated to vascular risk factors, signs and symptoms suggestive of infection, or presentation with stroke or transient ischemic attack. Similar to results of prior studies, 12,15,20 we found that vascular infection with C pneumoniae appears to be asymptomatic.…”
Section: Discussionsupporting
confidence: 91%
“…Infection appeared to be unrelated to vascular risk factors, signs and symptoms suggestive of infection, or presentation with stroke or transient ischemic attack. Similar to results of prior studies, 12,15,20 we found that vascular infection with C pneumoniae appears to be asymptomatic.…”
Section: Discussionsupporting
confidence: 91%
“…In patients undergoing carotid endarterectomy, the plaques were investigated for C. pneumoniae and the blood was examined for antichlamydial antibodies. Associated with symptomatic disease was a highlevel of antichlamydial IgA, whereas no association between C. pneumoniae presence in the plaque and symptomatic disease could be detected (52).…”
Section: Infectious Pathogens (I) Helicobacter Pylorimentioning
confidence: 83%
“…Reviewing the literature on the use of AmpliTaq Gold DNA polymerase in C. pneumoniae PCR assays, we found that in the majority of the studies, the type of DNA polymerase enzyme used was not identified. In a study that explicitly mentioned the use of AmpliTaq Gold DNA polymerase, the detection rate of C. pneumoniae DNA was 14.8% (30).…”
Section: Discussionmentioning
confidence: 99%